Diabetes Management among Type 2 DM Patient: Descriptive Study - Ni Wayan Trisnadewi; Oktaviani Ni Putu, Wiwik; Ni Komang Ayu Resiyanthi (Future Science, 2024)
Introduction: The primary issue facing diabetes patients today is the lack of adherence to their treatment plans. The high prevalence of diabetes poses a significant challenge for both patients and their fami-lies. This study aims to describe medication adherence, dietary habits, and physical exercise among patients with type 2 diabetes.Methods: This study is a descriptive analysis involving 82 partici-pants selected through a purposive sampling technique. The study in-cluded patients with type 2 diabetes mellitus who had been diagnosed for at least one year, lived with their families, and did not have any men-tal health issues. Data collection was conducted by visiting respondents at their homes. The questionnaire was administered with the assis-tance of a researcher and an enumerator, taking approximately 20 to 25 minutes to complete.Results: The study found that nonadherence to diet, medication, and exercise among type 2 diabetes patients remains high, with rates of 73.2%, 72.0%, and 61.0%, respectively.Conclusion: Patients with type 2 diabetes mellitus who have been diagnosed for more than one year exhibit poor diabetes management. These patients struggle to maintain a consistent medication and die-tary schedule and fail to engage in regular physical exercise.